Lichen aureus. Ultrastructural study in two pediatric patients. - Paradisi, M.; Angelo, C.; Cianchini, G.; Conti, G.; Onetti Muda, A.; Puddu, P. (European Journal of Pediatric Dermatology, 2018)
The Authors report two pediatric patients with lichen aureus. Lichen aureus is a skin disease whose etiology and pathogenesis has not yet been fully elucidated. However, it should be included in the chapter of pigmented purpuric angiodermatoses. The Authors describe the main clinical features and pathological findings and discuss its causes in the light of the most recent literature.